Efeito imediato da aplicação da bandagem funcional sobre a ativação muscular do membro inferior de mulheres com os pés planos - Cunha, Taís Lupino [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The aim of the study was to analyze the immediate effect of the application of functional bandage on the muscle activation of the lower limb of young women with a shortened medial longitudinal plantar arch. Fifteen women with flat feet participated in this study (age = 21 ± 2.0 years, body mass = 56.5 ± 8.9 kg, height 1.58 ± 0.06 meters, body mass index 22.4 ± 2, 4 kg.m-2). The Chippaux-Smirak Index was calculated using footprints. Then, the participants performed the Step Down Test before and after the application of rigid and elastic bandage techniques on the tested lower limb. Electromyographic data were collected during the execution of this test. The average activation of the three intermediate movements of descending the step was calculated for each muscle, in the conditions with and without bandage. Student's t-test for dependent samples was used to compare the electromyographic variables between the conditions with and without application of the bandage. There was a statistically significant decrease (p≤0.05) in the activation of the tibialis anterior and medial gastrocnemius muscles in the bandaged condition. Thus, the data from the present study, under the methodological conditions used, allow us to conclude that the use of functional bandages provides a decrease in the activation of muscles related to the ankle, which suggests that it is a viable intervention in cases of flat feet.

O objetivo do estudo foi analisar o efeito imediato da aplicação da bandagem funcional sobre a ativação muscular do membro inferior de mulheres jovens com o arco plantar longitudinal medial diminuído. Participaram deste estudo 15 mulheres com pés planos (idade= 21± 2,0 anos, massa corporal= 56,5 ± 8,9 Kg, estatura 1,58 ± 0,06 metros, Índice de Massa Corporal 22,4 ± 2,4 Kg.m-2). Foi calculado o Chippaux Smirak Index, por meio da impressão plantar. Em seguida, as participantes executaram o Step Down Test antes e após a aplicação das técnicas de bandagem rígida e elástica no membro inferior testado. Os dados eletromiográficos foram coletados durante a execução deste teste. A média da ativação dos três movimentos intermediários de descida do degrau foi calculada para cada músculo, nas condições com e sem bandagem. O teste t-Student para amostras dependentes foi utilizado para comparar as variáveis eletromiográficas entre as condições com e sem aplicação da bandagem. Houve diminuição estatisticamente significativa (p≤0,05) na ativação dos músculos tibial anterior e gastrocnêmio medial na condição com bandagem. Assim, os dados do presente estudo, nas condições metodológicas empregadas, permitem concluir que a utilização de bandagens funcionais proporcionam diminuição na ativação de músculos relacionados ao tornozelo, o que sugere ser uma intervenção viável em casos de pé plano.
Immediate effect of application of functional bandage on lower limb muscle activation in women with flat feet
Keywords: Bandage; Flat foot; Muscle activation; Bandagem; Pé plano; Ativação muscular